Adjuvant Tyrosine Kinase Inhibitors in Renal Cell Carcinoma: A Concluded Living Systematic Review and Meta-Analysis. (2021) - Riaz, Irbaz Bin; Siddiqi, Rabbia; Islam, Mahnoor; He, Huan; Riaz, Anum; Asghar, Noureen; Naqvi, Syed Arsalan Ahmed; Warner, Jeremy L.; Murad, Mohammad H.; Kohli, Manish
Abstract : PURPOSE: Multiple large clinical trials have investigated adjuvant tyrosine kinase inhibitors (TKIs) to reduce the risk of cancer recurrence and progression to metastasis in high-risk renal cell carcinoma. We sought to maintain living and interactive evidence on this topic, until a high level of certainty is reached for key clinical outcomes such that further updates become unnecessary and unlikely to change clinical practice. METHODS: We created a living interactive evidence synthesis platform to maintain a continuously updated meta-analysis on TKI monotherapy in adjuvant renal cell carcinoma. We implemented an automated search strategy with weekly updates to identify randomized phase 2 and 3 clinical trials. Study selection, appraisal, and data extraction were done in duplicate. Cumulative meta-analysis was performed using Analyzer Module in Living Interactive Evidence platform. For each outcome (overall survival [OS], disease-free survival [DFS], and all-cause and treatment-related adverse events), we assessed certainty of evidence using GRADE approach and conducted trial sequential analysis. RESULTS: This final update includes five randomized trials including recently updated data from PROTECT trial. Meta-analysis shows that adjuvant TKI monotherapy offers no benefit in OS (hazard ratio, 1.01; 95% CI, 0.91 to 1.12, high certainty) or DFS (hazard ratio, 0.92; 95% CI, 0.86 to 1.00, high certainty) and significantly increases adverse event risk. Lack of benefit was consistent across subgroups including highest-risk patients (test for subgroup differences: P = .32). Optimal information size criteria were met, and there was high certainty of evidence for lack of DFS and OS benefit for adjuvant TKIs. CONCLUSION: There is no guidance on when to stop maintaining a living review. In this example, we used trial sequential analysis and high certainty of evidence (future clinical trials unlikely to change current conclusions) as a benchmark to conclude a living review in view of convincing evidence.